PENGARUH PENERAPAN MODEL GAME-BASED LEARNING BERBANTUAN MEDIA SPIN OR SKIP TERHADAP MOTIVASI BERPRESTASI PESERTA DIDIK - Citra Nailus Sa'ida Rahma; Sri Sumaryati (Universitas Sebelas Maret, 2024)
AbstractThis study aims to examine the effect of implementing a game-based learning model assisted by spin or skip media on the achievement motivation of financial and institutional accounting students. Quantitative research using quasi-experiment research methods with a sample of 71 students from a population of 105 students. Sampling was conducted using the cluster random sampling technique. The research instrument employed was a achievement motivation questionnaire which was then analyzed using the prerequisite analysis test, namely the normality test using the Kolmogorov-Smirnov test and the homogeneity test using the Levene-Statistics test. Hypothesis testing was conducted using an independent sample t-test. The results of the independent sample t-test indicated that there was a statistically significant effect of applying game-based learning with the help of spin or skip media on students' achievement motivation. The independent sample t-test yielded the value of t-statistics = 2,098 with a significance value of 0.040, which was less than the 0.05 threshold.Keywords: Game-based learning, Spin or Skip, Achievement MotivationAbstrakPenelitian ini bertujuan untuk menguji pengaruh penerapan model game-based learning berbantuan media spin or skip terhadap motivasi berprestasi peserta didik Akuntansi Keuangan dan Lembaga. Penelitian kuantitatif menggunakan metode penelitian Quasi Experiment dengan sampel sebanyak 71 peserta didik dari populasi 105 peserta didik. Pengambilan sampel menggunakan teknik cluster random sampling. Instrumen penelitian menggunakan angket motivasi berprestasi yang selanjutnya dianalisis menggunakan uji prasyarat analisis yaitu dengan uji normalitas menggunakan uji Kolmogorov Smirnov dan uji homogenitas menggunakan uji Levene Statistic. Uji hipotesis menggunakan uji independent sample t-test. Hasil penelitian menunjukkan bahwa berdasarkan uji independent sample t-test terdapat pengaruh yang signifikan penerapan game-based learning dengan bantuan media spin or skip terhadap motivasi berprestasi peserta didik. Uji independent sample t-test menunjukkan nilai t hitung = 2,098 dengan signifikansi 0,040<0,05.Kata Kunci: Game-based Learning, Spin or Skip, Motivasi Berprestasi